Peculiarities of Non-Traditional Lessons: Keunikan Pelajaran Non-Tradisional - Karimova Sadoqat Sharobiddin (Universitas Muhammadiyah Sidoarjo, 2022)
This scientific study systematically examines the impact of student-centered learning in education, focusing on the conscious and active assimilation of knowledge and the organization of students based on their individual characteristics. The goals of this research are to identify and evaluate the didactic requirements necessary for effective teaching. Employing a comprehensive approach, both the advantages and disadvantages of this educational approach are thoroughly investigated. The study employs qualitative and quantitative methods to gather data, including surveys, interviews, and classroom observations. Results indicate that student-centered learning fosters solid knowledge assimilation and active student participation. The implication of these findings suggests that educators should consider implementing student-centered teaching strategies to enhance the overall learning experience. This research contributes to the existing body of knowledge on educational practices and provides valuable insights for educators, policymakers, and researchers aiming to improve teaching methodologies. Highlights: Student-centered learning: This study focuses on the effectiveness of student-centered learning in education, emphasizing the importance of placing students at the center of the learning process. Didactic requirements: The research examines the necessary didactic requirements for successful teaching, highlighting the significance of tailoring educational approaches to individual student characteristics. Knowledge assimilation and active participation: The study highlights the positive outcomes of student-centered learning, particularly in terms of solid knowledge assimilation and the promotion of active student participation. Keywords: Education, Student-centered learning, Didactic requirements, Knowledge assimilation, Active student participation.